2022
DOI: 10.1101/2022.06.04.494799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Density-dependent selection at low food levels leads to the evolution of population stability in Drosophila melanogaster even without a clear r-K trade-off

Abstract: Density-dependent selection, especially together with r-K trade-offs, has been one of the most plausible suggested mechanisms for the evolution of population stability. However, experimental support for this explanation has been both meagre and mixed. One study with Drosophila melanogaster yielded no evidence for populations adapted to chronic larval crowding having also evolved greater population stability. Another study, on D. ananassae, suggested that populations adapted to larval crowding evolved both grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our results essentially confirmed the insight of Dey et al (2012) that Drosophila populations adapting to chronic larval crowding at high versus low food amounts are likely to differ in whether or not they also evolve greater population stability attributes as a correlated response to density-dependent selection. In terms of demographic attributes and population stability characteristics, we found that the LCUs, adapted to larval crowding at relatively high food amounts, had evolved a different pattern of responses relative to controls than the MCUs (Pandey and Joshi 2022), which were adapted to larval crowding at very low food amounts. The LCUs did not evolve higher constancy than controls (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our results essentially confirmed the insight of Dey et al (2012) that Drosophila populations adapting to chronic larval crowding at high versus low food amounts are likely to differ in whether or not they also evolve greater population stability attributes as a correlated response to density-dependent selection. In terms of demographic attributes and population stability characteristics, we found that the LCUs, adapted to larval crowding at relatively high food amounts, had evolved a different pattern of responses relative to controls than the MCUs (Pandey and Joshi 2022), which were adapted to larval crowding at very low food amounts. The LCUs did not evolve higher constancy than controls (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The MCUs exhibited elevated realized population growth rates, compared to MB controls, across a wide range to medium to high densities, spanning both below and above the equilibrium populations size (Fig. 5 in Pandey and Joshi 2022). As noted by Pandey and Joshi (2022), this kind of change cannot be accommodated within the framework of even the θ -Ricker or θ -logistic models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations